2015
DOI: 10.1002/jbmr.2435
|View full text |Cite
|
Sign up to set email alerts
|

Legg-Calvé-Perthes Disease Produces Chronic Hip Synovitis and Elevation of Interleukin-6 in the Synovial Fluid

Abstract: Legg-Calvé-Perthes disease (LCPD) is a childhood hip disorder of ischemic osteonecrosis of the femoral head. Hip joint synovitis is a common feature of LCPD, but the nature and pathophysiology of the synovitis remain unknown. The purpose of this study was to determine the chronicity of the synovitis and the inflammatory cytokines present in the synovial fluid at an active stage of LCPD. Serial MRI was performed on 28 patients. T2-weighted and gadolinium-enhanced MR images were used to assess synovial effusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 17 publications
2
36
0
2
Order By: Relevance
“…There are several etiologic risk factors such as trauma [3, 4], excessive corticosteroid use [57], excessive alcohol intake [8], Legg-Calve-Perthes disease [9, 10], etc. Debilitated blood supply to the femoral head commonly leads to necrosis and collapse of the femoral head [11].…”
Section: Introductionmentioning
confidence: 99%
“…There are several etiologic risk factors such as trauma [3, 4], excessive corticosteroid use [57], excessive alcohol intake [8], Legg-Calve-Perthes disease [9, 10], etc. Debilitated blood supply to the femoral head commonly leads to necrosis and collapse of the femoral head [11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the radiological appearance of the synovial osteochondromatosis was very much in keeping with the classical appearance of primary synovial osteochondromatosis, that is, multiple loose bodies of similar size. As Legg–Calve–Perthes disease has been described in association with osteochondritis dissecans [7] and with chronic synovitis [8] and since these conditions have been associated with secondary synovial osteochondromatosis [1], we assume that the changes associated with Legg–Calve–Perthes in our case render secondary synovial osteochondromatosis the more likely diagnosis. Nonetheless, secondary synovial chondromatosis can only be distinguished histologically from primary synovial chondromatosis [3]; however, a histological specimen was not obtained in this patient.…”
Section: Discussionmentioning
confidence: 69%
“…Osteonecrosis of the femoral head is associated with synovitis characterized by a series of inflammatory cells and proinflammatory cytokines in necrotic lesion and synovium [33,34]. Previous research has found that the synovium is saturated by CD4+ T cells, macrophages, and some CD8+ T cells during the ONFH pathogenesis [35].…”
Section: Prp Treatment Inhibits Inflammatory Reaction In Onfhmentioning
confidence: 99%